Subtercola endophyticus sp. nov., a cold-adapted bacterium isolated from Abies koreana - Lingmin Jiang; Yuxin Peng; Jiyoon Seo; Doeun Jeon; Mi Gyeong Jo; Ju Huck Lee; Jae Cheol Jeong; Cha Young Kim; Hyeong Cheol Park; Jiyoung Lee (Scientific Reports, 2022)
Abstract A novel Gram-stain-positive, aerobic bacterial strain, designated AK-R2A1-2 T, was isolated from the surface-sterilized needle leaves of an Abies koreana tree. Strain AK-R2A1-2 T had 97.3% and 96.7% 16S rRNA gene sequence similarities with Subtercola boreus K300T and Subtercola lobariae 9583bT, respectively, but formed a distinct phyletic lineage from these two strains. Growth of strain AK-R2A1-2 T was observed at 4–25 °C at pH 5.0–8.0. Strain AK-R2A1-2 T contained menaquinone 9 (MK-9) and menaquinone 10 (MK-10) as the predominant respiratory quinones. The major cellular fatty acids were anteiso-C15:0 and summed feature 8 (C18:1ω7c or/and C18:1ω6c), and the polar lipids included diphosphatidylglycerol (DPG) and three unknown aminolipids, AKL2, AKL3, and AKL4. The complete genome of strain AK-R2A1-2 T was sequenced to understand the genetic basis of its survival at low temperatures. Multiple copies of cold-associated genes involved in cold-active chaperon, stress response, and DNA repair supported survival of the strain at low temperatures. Strain AK-R2A1-2 T was also able to significantly improve rice seedling growth under low temperatures. Thus, this strain represents a novel species of the genus Subtercola, and the proposed name is Subtercola endophyticus sp. nov. The type strain is AK-R2A1-2 T (= KCTC 49721 T = GDMCC 1.2921 T).